(untitled) (Integral Research, 2025)
Centuries have passed since the performance of Shakespearean plays, but still, they continue to fascinate the critics and readers for their relevance even in today’s world. Recently, critics and scholars have endeavoured to interpret Shakespeare from an ecological viewpoint with the emergence of ‘Environmental Humanities’. Shakespeare never used the term ecology or environmentalism in his works but his employment of natural elements somehow replicates the environmental crisis which we are facing today. Shakespeare manifested his genius in his treatment of supernatural elements like fairies, goblins, and witches and his A Midsummer Night’s Dream has widely been acclaimed by the audience and critics for its magnificent use of supernatural creatures like fairies. The present study aims to demonstrate how the forest, the fairies and the fairy world are presented by Shakespeare in A Midsummer Night’s Dream. This paper will investigate how Nick Bottom manifests civilization’s departure from the world of nature and its re-aggregation into the civilized world order after fully realizing its deep bonding with other beings of nature. In this journey of self-realization, human-turned-donkey Bottom is transformed into an ecological self and Puck or Robin Goodfellow, the embodiment of nature, heralds the nature identification.